The importance of human rights (HAM) in providing protection to victims of bullying and assessing the various impact for victims - Ghani Wahyu Riyasa; Hamid Reza Asefi (Requisitoire Law Enforcement, 2023)
Bullying often occurs in the area of group environment, especially in the school environment and it is an act that violates human rights, because human rights are the moral and legal basis that protects every individual from unfair and discriminatory treatment.Protecting victims of bullying and preventing such acts is a task that is not only the responsibility of individuals.We use a research method in the form of literature analysis to explore the importance of human rights in fighting bullying and to identify the psychological effects that may be experienced by victims of bullying. Human rights provide protection for victims of bullying by recognising their right to live in a safe environment free from discrimination. Psychological impacts include stress, anxiety, and depression, while social impacts involve isolation, decreased self-confidence, and impaired social relationships. Physical impacts include physical injuries and health disorders associated with chronic stress. Human rights protection and social support are important to counter bullying and protect the well-being of victims. this research highlights the importance of human rights in protecting victims of bullying. Human rights include the victim's right to live in a safe environment, get legal protection, be free from discrimination, privacy, and remedy, and get an education without harassment. This creates a strong legal and moral basis to protect victims of bullying and prevent such acts.